РAPILLOMAVIRUS INFECTION AND BACTERIAL VAGINOSIS: IMMUNOMODULATING THERAPY IN PREGNANT - Елена Николаевна Кравченко; Лариса Владимировна Куклина; Ольга Юрьевна Цыганкова (The Publishing House Medicine and Enlightenment, 2018)
Purpose of the study - optimization of the tactics of managing pregnant women with bacterial vaginosis and papillomavirus infection caused by various types of human papillomavirus by correcting local immunity with the use of the drug Viferon (recombinant interferon-alpha2b). Material and methods. The main group (n = 100) consisted of patients with PVI in combination with BV, which was performed at the first stage with the sanation of the vagina metronidazole, in the second stage - immunomodulatory therapy with the drug Viferon. The comparison group (n = 100) consisted of pregnant women with PVI in combination with BV, who conducted only a course of metronidazole therapy. Results. It was found that in the pregnant group of the main group after the combined treatment, abnormal colposcopic manifestations were noted only in 26 % of cases. In comparison group patients, statistically significant differences were not observed against the background of the therapy, characterizing the regression of abnormal colposcopic pictures within the group (46 %). At a repeated examination in 36 weeks. According to the results of cytological studies, it was noted that in women of the main group, the pathological values (HSIL, NILM, ASCUS) regressed from 80 % to 33 % (p < 0.01), the remaining patients showed stabilization of the process.In the comparison group, the indices also improved, but to a lesser extent from 78 % to 52 % (p > 0.05). An abnormal colposcopic pattern was defined in the main group in 75 %, in the comparison group in 72 %, after treatment these data were obtained in 26 % and 46 %, respectively (p < 0.01). In the comparison group, a second episode of bacterial vaginosis was observed in 24 % of women 4-7 weeks after treatment, in the main group of recurrences it was not noted (p < 0,01). The conclusion. In the study, an analysis of the indicators characterizing the severity of manifestations of papillomavirus infection and bacterial vaginosis against the background of pregnancy shows that the use of a combined treatment regimen with the inclusion of immunomodulatory therapy with the drug Viferon is more effective than monotherapy.